2010
DOI: 10.2193/2009-105
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Assessment of Vehicle Disturbance Effects on Migratory Shorebirds

Abstract: Off-road vehicle (ORV) traffic is one of several forms of disturbance thought to affect shorebirds at migration stopover sites.Attempts to measure disturbance effects on shorebird habitat use and behavior at stopover sites are difficult because ORV disturbance is frequently confounded with habitat and environmental factors. We used a before-after-control-impact experimental design to isolate effects of vehicle disturbance from shorebird responses to environmental and habitat factors. We manipulated disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Because of this, it was impossible to carry out a proper BACI study, which would be essential to fully demonstrate whether or not there were any significant impacts (e.g. Tarr et al 2010). Nevertheless, our results are still useful to suggest that wetland bird abundances at present are not lower at <500 m from the railway than elsewhere in the estuary, though they cannot be used to make comparisons in relation to the situation before the construction of the railway.…”
Section: Discussionmentioning
confidence: 91%
“…Because of this, it was impossible to carry out a proper BACI study, which would be essential to fully demonstrate whether or not there were any significant impacts (e.g. Tarr et al 2010). Nevertheless, our results are still useful to suggest that wetland bird abundances at present are not lower at <500 m from the railway than elsewhere in the estuary, though they cannot be used to make comparisons in relation to the situation before the construction of the railway.…”
Section: Discussionmentioning
confidence: 91%
“…Classic models of human disturbance to birds posit that vehicles evoke responses from wildlife that are less frequent or intense than those evoked by pedestrians [24,52]. These models do, however, rarely consider the speed or distance covered by vehicles, the large number of vehicles in some parks, and the rate at which they encounter wildlife, but see 20,23 - all factors that contribute to the considerable disturbance effects recorded here.…”
Section: Discussionmentioning
confidence: 98%
“…Like other vertebrates, beach-dwelling birds are prone to disturbance when they encounter potentially threatening stimuli, such as humans engaged in recreational activities [21]. On beaches, vehicles also potentially crush eggs and young and cause fatal collisions with birds [22,23]. Lowered reproductive success and adult survival are key demographic parameters which potentially influence population viability, thus the impacts of vehicles potentially represent conservation threats to populations of beach-dwelling fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance behavior in foraging birds is demonstrated by watching the responses of shorebirds to stressors that are on beaches (Pfister et al, 1992), by either (1) waiting opportunistically for a new disturbance to occur and observing bird responses (Burger et al, 2004), or (2) experimentally approaching foraging shorebirds either by walking or driving a vehicle (Yasue, 2005a(Yasue, , 2005bTarr et al, 2010). Madsen (1998) showed that waterfowl that were not protected by law used hunting-free areas more often than those where hunting was allowed, although protected species showed no differences.…”
Section: New Disturbancesmentioning
confidence: 99%
“…Several types of activities affect shorebirds, including direct effects from human disturbance, habitat loss and prey depletion, and indirect effects from fishing or tourist activities (Burger et al, 2007;Niles et al, 2008;Piersma et al, 2001;Baker et al, 2004). Predicting the impact of human disturbance to flocks of shorebirds usually involves observing the immediate effects of individuals or other stressors on shorebird foraging (Tarr et al, 2010), although Gill et al (2001) suggested that behavioral responses alone may not reflect population consequences. Subsequently, GossCustard et al (2006) provided a test for oystercatchers (Haemoatopus ostralegus) that indicated that disturbances (e.g., raptors) significantly reduced fitness, although this conclusion needs to be examined for other species, in other ecosystems.…”
mentioning
confidence: 99%